Effect of platelet inhibitors on thrombus burden in patients with acute pulmonary embolism. (2nd January 2021) - Van Galen, Joseph; Pava, Libia; Wright, Colin; Elbadawi, Ayman; Hamer, Annelise; Chaturvedi, Abhishek; Cameron, Scott J.
Abstract: Venous thromboembolism (VTE) whether provoked or not can be life-threatening due to an acute increase in load on the right ventricle (RV) from obstruction of the pulmonary artery (PA). Treatment for and prevention of VTE involves anti-thrombotic agents; more specifically, medications targeting the anticoagulation cascade. In spite of the widespread acceptance of anticoagulants in the treatment of VTE, there appears to be an ongoing belief that platelet reactivity contributes to thrombus burden in patients with acute pulmonary embolism (PE). This investigation of 398 patients presenting with acute PE evaluated whether anti-platelet medication use, which consisted mostly of aspirin therapy, at the time of presentation, affects PA thrombus burden, RV load, or short-term patient outcomes. We conclude that platelets may have been erroneously incriminated as direct thrombotic mediators in patients with acute PE since aspirin neither decreased PA thrombus burden, nor did aspirin improve short-term mortality following acute PE.